The Concept of Contract: “Convergence” or “Divergence” between the Legal System and the Islamic System - Nassakh, Fatima (Journal of Legal Studies and Researches, 2017)
This study focuses on the concept of the contract between the legal system and the Islamic system, and the search for convergence or divergence between the two systems. We started with the idea of ​​defining the contract in order to determine the meaning in both systems and we concluded that the concept is different. We examined other concepts in order to find convergence or divergence between the two systems. Among these concepts are what is known as contractual will and the principle of the contract being the law of the contracting parties. In our study of the two ideas in each system, we noticed the extent of the difference between them.